Company Value: A Review of the Financial Performance of Property and Real Estate Companies - Tenriwaru Tenriwaru; Sri Buana; Syamsu Alam; Asriady Bakri (AJAR, 2024)
This research was conducted with the aim of analyzing financial performance based on profitability ratio analysis, liquidity ratios analysis, and solvency ratio analysis in increasing firm value. This research uses descriptive quantitative method. The sampling method was purposive sampling, consisting of 2 samples of companies in the Property and Real Estate Sector: (1) PT. Ciputra Development Tbk and (2) PT. Summerecon Agung Tbk. The results of this study indicate that: (1) PT Ciputra Development Tbk and PT Summarecon Agung Tbk tend to have almost stagnant ROA values and even decrease in each period of the current year. (2) Liquidity (CR) from 2018-2022 PT Ciputra Development Tbk and PT Summarecon Agung Tbk have a current ratio percentage above the industry standard which is more than 100%, this condition shows that these companies can control their current debt. (3) PT Ciputra Development Tbk and PT Summarecon Agung Tbk shows that the percentage of DER from year to year tends to be high above 90% of the industry standard, this condition results in the company's debt ratio being higher than the company's capital.